3Dive: An Immersive Environment for Interactive Volume Data Exploration - Boyles, Michael; Fang, Shiaofen (International Journal of Virtual Reality, 2001)
This paper describes an immersive system, called 3DIVE, for interactive volume data visualization and exploration inside the CAVE virtual environment. Combining interactive volume rendering and virtual reality provides a natural immersive environment for volumetric data visualization. More advanced data exploration operations, such as object level data manipulation, simulation and analysis, are supported in 3DIVE by several new techniques: volume primitives and texture regions are used for the rendering, manipulation, and collision detection of volumetric objects; the region based rendering pipeline is integrated with 3D image filters to provide an image-based mechanism for interactive transfer function design; a collaborative visualization module allows remote sites to collaborate over common datasets with passive or active view sharing. The system has been recently released as public domain software for CAVE/ImmersaDesk users, and is currently being actively used by a 3D microscopy visualization project.